Circular Business Model Transformation: A Roadmap for Incumbent Firms. (February 2019) - Frishammar, Johan; Parida, Vinit
To achieve positive economic, environmental, and social benefits, many incumbent manufacturing firms attempt to apply circular economy principles to their business practices. However, these firms often struggle to change their existing linear business models to circular models because the steps required for successful transformation are still poorly understood. Based on a multiple case study of eight business model transformation journeys, this article proposes a roadmap for circular business model transformation. It provides a step-by-step process to enable circular transition, allowing companies to meet environmental, social, and financial objectives and proactively address sustainability.